Vector fields of zero total curvature of the second type in fore-dimension space; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Onishchyk N. М. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа